Civil Liability of E-Commerce Platforms for the Sale of Counterfeit Industrial Design Products (A Study on the Protection of Rights Holders in the Digital Economic Ecosystem) - Mellysyah Dewi Sartika Siregar; Siti Nur Fadillah; Nova Syafitri; Nadiva Armayani; Cindy Mutiara Putri (ISNU Sumatera Utara, 2025)
This study aims to analyze the civil liability of e-commerce platforms for the rampant sale of counterfeit industrial design products in the digital economy ecosystem. Although platforms act as intermediaries, their presence often becomes a means of industrial design rights violations that harm legitimate rights holders. The research method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that the legal standing of e-commerce platforms in civil law can be classified as electronic means providers who have subjective supervision obligations. Forms of industrial design violations in the marketplace generally take the form of imitation of the configuration, shape, and composition of products sold by third parties. The analysis of the platform's civil liability refers to the Safe Harbor Policy principle, but platforms can be held accountable through the doctrine of Unlawful Acts (PMH) if proven negligent or allowing infringing content to remain available after a report (notice and take down). Legal protection for rights holders includes preventive protection through the platform's IPR verification system and repressive protection in the form of civil compensation claims.